Wild Mushrooms: A Hidden Treasure of Novel Bioactive Compounds - Gebreselema Gebreyohannes; Desta Berhe Sbhatu (International Journal of Analytical Chemistry, 2023)
Secondary metabolites are hidden gems in mushrooms. Understanding these secondary metabolites’ biological and pharmacological effects can be aided by identifying them. The purpose of this work was to profile the mycochemical components of the extracts of Auricularia auricula judae, Microporus xanthopus, Termitomyces umkowaani, Trametes elegans, and Trametes versicolor to comprehend their biological and pharmacological capabilities. Mushroom samples were collected from Kenya’s Arabuko–Sokoke and Kakamega National Reserved Forests and identified using morphological and molecular techniques. Chloroform, 70% ethanol, and hot water solvents were used to extract the mycochemical components. Gas chromatography mass spectrometry (GC-MS) was used to analyze the chloroform, 70% ethanol, and hot water extracts of all the species examined. A total of 51 compounds were isolated from all extracts and classified as carboxylic acids, esters, phenols, fatty acids, alcohol, epoxides, aldehydes, fatty aldehydes, isoprenoid lipids, and steroids. Tetracosamethyl-cyclododecasiloxane (18.90%), oleic acid (72.90%), phenol, 2, 6-bis (1, 1-dimethylethyl)-4-methyl-, and methylcarbamate (26.56%) were all found in high concentrations in A. auricular judae, M. xanthopus, T. umkowaani, T. elegans, and T. versicolor, respectively. Fatty acids make up the majority of the compounds isolated from the T. elegans chloroform extract and the T. umkowaani 70% ethanol extract, respectively. Particularly, these fatty acids play crucial roles in the anti-inflammatory, hypocholesterolemic, anticancer, and antibiofilm formation activities. These bioactive elements indicate that the extracts of five wild mushrooms may be reliable sources of secondary metabolites for therapeutic development. Therefore, additional research is required to comprehend the usefulness of these chemicals in many functional areas and to improve the present understanding of macrofungi.